Electrolyte for sodium ion battery and sodium ion battery

By using electrolytes prepared by ether solvents and sodium salts, the solubility and antioxidant capacity of sodium salts are enhanced, and the problem of stable circulation of sodium ion batteries in high pressure and wide temperature ranges is solved, achieving efficient battery performance improvement.

CN119905668APending Publication Date: 2025-04-29BEIHANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510045238.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing sodium ion batteries are difficult to circulate stably in high voltage and wide temperature domains, especially negative-electrode sodium ion batteries have challenges in high energy density and temperature adaptability.

Method used

The electrolyte prepared by ether solvents and sodium salts is enhanced by the anionic effect of ether solvents and sodium salts, which improves the solubility and antioxidant capacity of sodium salts, thereby improving the working voltage and stability of the battery.

Benefits of technology

The stable circulation of a wide temperature domain high-pressure sodium ion battery in the range of -20 to 60°C is achieved, and the Coulomb efficiency, mass specific capacity and capacity retention rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905668A_ABST
    Figure CN119905668A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte for a sodium ion battery. The electrolyte is prepared by using an ether solvent and sodium salt as raw materials. The ether solvent and the sodium salt have relatively high solvation entropy, so that the dissolution of the sodium salt is promoted, and the electrolyte has relatively high ionic conductivity in a wide temperature range. Meanwhile, the sodium salt is dissolved in the ether electrolyte to form a solvation structure rich in anions, so that a stable electrode-electrolyte interface is formed. Therefore, the obtained electrolyte not only has good compatibility with a sodium metal negative electrode and a high-voltage positive electrode, but also can improve the coulombic efficiency of the sodium-ion battery in a wide temperature range, thereby improving the comprehensive performance of the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to an electrolyte for a wide temperature range high-voltage sodium ion battery and a wide temperature range high-voltage sodium ion battery. Background Art

[0002] Sodium-ion batteries are a new type of energy storage device that has attracted widespread attention after lithium-ion batteries. They have the advantages of low cost and abundant resources. In sodium-ion batteries, the electrolyte is mainly composed of solutes, solvents and additives, which affect battery safety, battery energy density, cycle life and rate performance.

[0003] At present, sodium ion batteries use a variety of ether and ester solvents to prepare electrolytes. Their oxidation and reduction stability needs to be improved, and their usable temperature is relatively narrow, making them prone to oxidation and decomposition to produce gas under high voltage or repeated cycles, and unable to circulate stably under wide temperature range and high pressure conditions.

[0004] Among them, anode-free sodium-ion batteries (AFSMBs) are a new type of battery structure. In the battery preparation process, no negative electrode active materials are added, and only the negative electrode current collector is set as the nominal negative electrode. After the first charge is completed, the sodium ions (Na + ) migrates to the surface of the negative electrode current collector and forms a sodium negative electrode, that is, the positive electrode material is de-sodiumized and deposited in situ on the negative electrode current collector to form a real negative electrode. Negative electrode-free sodium ion batteries have shown great potential in the field of energy storage due to their high theoretical energy density, high safety, cost savings and simple manufacturing process.

[0005] However, in anode-free sodium-ion batteries, the lack of anode materials places higher requirements on the coulombic efficiency and uniform and dense deposition behavior of sodium metal deposition and stripping on the anode current collector. Secondly, in order to further improve the energy density of anode-free sodium-ion batteries, it is crucial to adopt energy-dense high-voltage cathodes. However, the stable operation of high-energy-density anode-free sodium-ion soft-pack batteries, especially under a wide temperature range, still faces great challenges, hindering the development of their practical applications.

[0006] As one of the key components of anode-free sodium-ion batteries, the development of wide-temperature and high-voltage electrolytes is expected to improve the cycle stability and ability of anode-free sodium metal batteries to operate over a wide temperature range. At present, in the development of anode-free sodium-ion batteries, sodium hexafluorophosphate + ether-based electrolytes are still the main choice for electrolytes of anode-free sodium batteries due to their high ionic conductivity and good sodium metal compatibility. However, the currently used "sodium salt + ether solvent" electrolyte cannot meet the stable cycle requirements of high-energy-density anode-free sodium-ion batteries over a wide temperature range. Therefore, the development of an electrolyte system suitable for anode-free sodium-ion batteries is an important strategy to improve the cycle stability and temperature adaptability of anode-free sodium-ion batteries, and is of great significance for improving the comprehensive performance of anode-free sodium-ion batteries and promoting their practical applications. Summary of the invention

[0007] In order to overcome the above problems, the present invention provides an electrolyte for sodium ion batteries, and uses the electrolyte to develop wide temperature range high-voltage sodium ion batteries, especially wide temperature range high-voltage negative electrode-free sodium ion batteries. Using the electrolyte obtained by the ether solvent and sodium salt provided by the present invention, the ether solvent and the anion in the sodium salt are enhanced, and a higher sodium salt solubility and antioxidant capacity are obtained. In the sodium ion battery, its actual working voltage is effectively improved, and the stability is good, and the coulomb efficiency, mass specific capacity, and capacity retention rate of the sodium ion battery are greatly improved. Battery performance, such as the capacity, capacity retention rate, etc., thereby realizing a wide temperature range high-voltage sodium ion battery within -20 to 60 ° C, especially a wide temperature range high-voltage negative electrode-free sodium ion battery.

[0008] The first aspect of the present invention aims to provide an electrolyte for a sodium ion battery, which is prepared using raw materials including an ether solvent and a sodium salt.

[0009] The ether solvent includes one or more of the ether compounds represented by the general formula (1),

[0010]

[0011] Among them, R1 and R2 are each independently selected from an alkyl group with a carbon number greater than 1, preferably an alkyl group with a carbon number of 4-6, more preferably a butyl group or a pentyl group, such as a butyl group, and further such as a n-butyl group. More preferably, R1 and R2 are both n-butyl groups; n is an integer of 1-10, preferably an integer of 1-5.

[0012] Optionally, the ether solvent further comprises one or more of the ether compounds represented by the general formula (2),

[0013]

[0014] Among them, R3 and R4 are each independently selected from an alkyl group with a carbon number greater than 1, preferably an alkyl group with a carbon number of 2-7, more preferably propyl, butyl, pentyl or hexyl, such as butyl, and further such as n-butyl, more preferably, R3 and R4 are both n-butyl; m is an integer of 1-10, preferably an integer of 1-5.

[0015] The sodium salt is selected from one or more sodium fluoride salts, preferably one or more inorganic sodium fluoride salts, more preferably one or more sodium hexafluoroarsenate, sodium hexafluorophosphate and sodium tetrafluoroborate, such as sodium hexafluorophosphate and / or sodium tetrafluoroborate.

[0016] The second aspect of the present invention aims to provide a method for preparing the electrolyte of the sodium ion battery, wherein the raw materials include the ether solvent and the sodium salt. Under a protective atmosphere, the sodium salt is added to the ether solvent after primary dehydration, dissolved, and solution I is obtained. Preferably, secondary dehydration is performed to obtain the electrolyte.

[0017] The third aspect of the present invention aims to provide a sodium ion battery, which comprises a positive electrode, an electrolyte, and a separator, wherein the electrolyte is one of the electrolytes for sodium ion batteries described in the first aspect.

[0018] The fourth aspect of the present invention aims to provide a method for preparing the sodium ion battery described in the third aspect, which is carried out under a protective atmosphere, such as an argon atmosphere.

[0019] The interior of the sodium-ion half-cell is assembled in the order of positive electrode, separator, sodium metal negative electrode or negative electrode current collector, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the sodium metal negative electrode.

[0020] The interior of the negative electrode-free sodium-ion battery is assembled in the order of positive electrode, separator, and negative electrode current collector, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the negative electrode current collector.

[0021] The non-sodium metal negative electrode sodium ion battery is assembled in the order of positive electrode, separator, and non-sodium metal negative electrode, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the non-sodium metal negative electrode.

[0022] The beneficial effects of the present invention include:

[0023] (1) The ether solvent in the present invention contains two or more ethylene oxide structural units and an alkyl group with a carbon number greater than 1 at both ends, especially an alkyl group with a carbon number greater than 3, so that the ether compound has a lower LUMO energy level (lowest unoccupied molecular orbital energy level), and has better dissolving ability than ethers containing a monoethylene oxide structure (such as ethylene glycol alkyl ether), and has good compatibility with sodium metal. As an electrolyte solvent, the electrolyte has good ionic conductivity in a wide temperature range, and the solvation energy for sodium ions is relatively low, which is conducive to the formation of anion-rich solvation structure, thereby forming a stable electrode-electrolyte interface.

[0024] (2) The ether solvent in the present invention and the sodium salt provided by the present invention can form an anion-rich solvation structure, thereby promoting the dissolution of the sodium salt. The obtained electrolyte not only has good compatibility in sodium ion batteries, but also has higher ionic conductivity.

[0025] (3) The ether solvents in the present invention have a relatively low solvation energy for sodium ions, so that they can form anion-rich solvation structures, thereby forming a stable electrode-electrolyte interface, which can improve the coulombic efficiency of sodium ion batteries in a wide temperature range, thereby improving the comprehensive performance of sodium ion batteries. In particular, diethylene glycol dibutyl ether has a high boiling point (about 256°C), an extremely low vapor pressure (about 0.0013Kpa) and a low freezing point (-60°C). The electrolyte prepared from it not only has good cycle stability at a temperature of -20 to 60°C, but also can increase the voltage of the sodium ion battery, for example, a 4.0V negative electrode-free sodium ion battery can be stably cycled in a temperature range of -20 to 60°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The coulombic efficiency statistics of the sodium ion half-cell 1# according to the present invention are shown when different cycle numbers are tested at -20°C, 25°C and 60°C respectively;

[0027] Figure 2 The sodium ion half-cell 1# of the present invention was charged and discharged for 10 cycles at -20°C, 25°C and 60°C, and then deposited 2 mAh cm -2 SEM image of the Na metal anode of sodium ion half-cell 1# after the area specific capacity was calculated;

[0028] Figure 3 The charge and discharge curves of the button-type negative electrode-free sodium ion battery 1# of the present invention at -20°C, 25°C and 60°C are shown;

[0029] Figure 4 The charge and discharge curves of the first and 100th cycles of the soft-package negative electrode-free sodium ion battery 1# of the present invention are shown. DETAILED DESCRIPTION

[0030] The present invention is further described below by way of embodiments. Through these detailed descriptions, the features and advantages of the present invention will become clearer and more specific. However, the scope of protection of the present invention is not limited to the following. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0031] The first aspect of the present invention provides an electrolyte for a sodium ion battery, which is prepared using raw materials including an ether solvent and a sodium salt. The sodium ion battery in the present invention is a secondary battery that relies on the movement of sodium ions between positive and negative electrodes to complete charging and discharging.

[0032] The ether solvent includes one or more of the ether compounds represented by the general formula (1),

[0033]

[0034] Among them, R1 and R2 are each independently selected from an alkyl group with a carbon number greater than 1, preferably an alkyl group with a carbon number of 4-6, more preferably a butyl group or a pentyl group, such as butyl, and further such as n-butyl, and more preferably, R1 and R2 are both n-butyl; n is an integer of 1-10, preferably an integer of 1-5, more preferably 1, 2 or 3, such as 1.

[0035] The carbon number in the R1 and R2 groups will affect the solubility of the sodium salt and the maximum cut-off voltage of the sodium ion battery. When R1 and R2 are alkyl groups with a carbon number greater than 1, due to their steric hindrance effect, the solvation structure of the sodium ions in the electrolyte is changed, and the maximum voltage that the sodium ion battery can reach can be appropriately increased; when the carbon number is 4 or more, the solubility is higher than when it is ethyl or propyl, and the maximum cut-off voltage of the sodium ion battery is increased. The ether compound containing two or more ethylene oxide structural units and alkyl groups with a carbon number greater than 1 at both ends, especially alkyl groups greater than 3, can make the ether compound have a lower LUMO energy level (lowest unoccupied molecular orbital energy level), and has better solubility than ethers containing a monoethylene oxide structure (such as ethylene glycol alkyl ethers), and has good compatibility. As an electrolyte solvent, the electrolyte has a higher ionic conductivity, and the solvation energy for sodium ions is relatively low, which is conducive to the formation of anion-rich solvation structure, thereby forming a stable electrode-electrolyte interface.

[0036] Optionally, the ether solvent further comprises one or more of the ether compounds represented by the general formula (2),

[0037]

[0038] Among them, R3 and R4 are each independently selected from an alkyl group with a carbon number greater than 1, preferably an alkyl group with a carbon number of 2-7, more preferably propyl, butyl, pentyl or hexyl, such as butyl, and further such as n-butyl, more preferably, R3 and R4 are both n-butyl; m is an integer of 1-10, preferably an integer of 1-5, more preferably 1, 2 or 3, such as 1.

[0039] Preferably, the ether solvent is selected from one or more of the ether compounds represented by general formula (1).

[0040]

[0041] Among them, R1 and R2 are each independently selected from an alkyl group with a carbon number greater than 1, preferably an alkyl group with a carbon number of 4-6, more preferably a butyl group or a pentyl group, such as butyl, and further such as n-butyl, and more preferably, R1 and R2 are both n-butyl; n is an integer of 1-10, preferably an integer of 1-5, more preferably 1, 2 or 3, such as 1.

[0042] The ether solvents in the present invention and the sodium salt provided by the present invention can form an anion-rich solvation structure, thereby promoting the dissolution of the sodium salt, and the obtained electrolyte not only has good compatibility in the sodium ion battery, but also makes the electrolyte have a higher ionic conductivity in a wide temperature range. The ether solvents in the present invention have a relatively low solvation energy for sodium ions, so that they can form an anion-rich solvation structure, thereby forming a stable electrode-electrolyte interface, which can improve the coulomb efficiency and cycle stability of the sodium ion battery in a wide temperature range, thereby improving the comprehensive performance of the sodium ion battery. In particular, diethylene glycol dibutyl ether has a higher boiling point (about 256°C), an extremely low vapor pressure (about 0.0013Kpa) and a lower freezing point (-60°C), and the electrolyte prepared therefrom not only makes the sodium ion battery have good cycle stability in the temperature range of -20 to 60°C, but also can improve the cut-off working voltage of the sodium ion battery, for example, a 4.0V negative electrode-free sodium ion battery can be stably cycled in the temperature range of -20 to 60°C.

[0043] The sodium salt is selected from one or more sodium fluoride salts, preferably one or more inorganic sodium fluoride salts, more preferably one or more sodium hexafluoroarsenate, sodium hexafluorophosphate and sodium tetrafluoroborate, such as sodium hexafluorophosphate and / or sodium tetrafluoroborate. The electrolyte salt used in the present invention and the above-mentioned ether solvent can maintain a high ionic conductivity of the electrolyte in a wide temperature range, construct a stable electrode-electrolyte interface (SEI and CEI), improve the cut-off operating voltage of the sodium ion battery, and improve the comprehensive performance of the sodium ion battery.

[0044] The special interaction between the cation and anion in the ether solvent of the present invention and the sodium salt of the present invention increases the solvation entropy of the sodium ion and effectively promotes the dissolution of the electrolyte salt. Especially when the R1 and R2 groups in the ether solvent molecules of the present invention are alkyl groups with a carbon number of 4-6, the anion effect with the sodium salt of the present invention can be enhanced, the solubility of the sodium salt is improved, and then the sodium salt solubility caused by the growth of the carbon chain is avoided to be reduced, and the problem of the electrolyte ion conductivity being significantly reduced. For example, when using diethylene glycol dibutyl ether as a solvent and sodium hexafluoroarsenate, sodium hexafluorophosphate and sodium tetrafluoroborate as sodium salts in the present invention, compared to diethylene glycol dimethyl ether, diethylene glycol diethyl ether and diethylene glycol dipropyl ether, not only the solubility of the sodium salt can be effectively improved, the ionic conductivity of the electrolyte is guaranteed to be higher in a wider operating temperature range, and the desolvation energy barrier of the sodium ion is reduced.

[0045] The second aspect of the present invention provides a method for preparing the electrolyte for sodium ion batteries, wherein the raw materials include the ether solvent and the sodium salt. Under a protective atmosphere, the sodium salt is added to the ether solvent after primary dehydration, dissolved, and solution I is obtained. Preferably, secondary dehydration is performed to obtain the electrolyte.

[0046] The protective atmosphere is a dehydrated and deoxygenated atmosphere, preferably an atmosphere in which the water and oxygen contents are both lower than 0.1 ppm, such as an argon atmosphere.

[0047] The primary dehydration is to add a dehydrating agent to the ether solvent for dehydration. The solid dehydrating agent is a water absorbing agent that does not react with the ether solvent, preferably selected from one or more of the molecular sieves. The mass ratio of the ether solvent to the dehydrating agent is (2-10):1, preferably (3-8):1, and more preferably (4-6):1. Preferably, after adding the dehydrating agent, the dehydration is allowed to stand for 12-48 hours, preferably 20-24 hours. After the primary dehydration, the molecular sieve is removed.

[0048] The secondary dehydration is performed by adding metallic sodium to solution I for dehydration.

[0049] The third aspect of the present invention further provides a sodium ion battery, which includes a positive electrode, an electrolyte, and a separator, wherein the electrolyte is one of the electrolytes for sodium ion batteries described in the first aspect.

[0050] The present invention does not specifically limit the positive electrode material of the sodium ion battery, and any positive electrode material that can be used for a sodium ion battery can be used. For example, one of an oxide-type positive electrode material, a polyanion-type positive electrode material, a Prussian blue positive electrode material, a Prussian white positive electrode material, and an organic positive electrode material, preferably one of a carbon-coated aluminum foil, a metal oxide-type positive electrode material, and a phosphate-based polyanion-type positive electrode material, specifically, a carbon-coated aluminum foil, a sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn1 / 3 O2, NFM), sodium iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium iron pyrophosphate, sodium vanadium fluorophosphate or sodium iron fluorophosphate, preferably carbon-coated aluminum foil, sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NFM) or sodium vanadium phosphate.

[0051] The present invention does not specifically limit the separator of the sodium ion battery, and any separator that can be used for the sodium ion battery can be used, such as a polymer separator, an inorganic solid electrolyte separator, and an inorganic modified polymer separator, such as a PE separator (polyethylene separator), a PE@Al2O3 separator (such as produced by Cluder), Celgard2500 (such as produced by Cluder), glass fiber (such as GF / D produced by Whatman), Al2O3@Celgard (such as produced by Cluder), preferably Al2O3@Celgard.

[0052] In sodium ion batteries, for button batteries, the amount of the electrolyte is 10-100 μL, preferably 10-80 μL, and more preferably 30-50 μL. For soft-pack batteries, the ratio of the mass of the electrolyte to the capacity of the sodium ion battery is 1-10 g / Ah, preferably 2-8 g / Ah, and more preferably 2-4 g / Ah.

[0053] The operating temperature of the sodium ion battery is -30°C to 70°C, preferably -25°C to 65°C, and more preferably -20°C to 60°C.

[0054] The sodium ion battery further includes a negative electrode current collector, a sodium metal negative electrode or a non-sodium metal negative electrode.

[0055] The present invention does not specifically limit the negative electrode current collector of the sodium ion battery, and any negative electrode current collector that can be used for the sodium ion battery can be used, such as copper foil, carbon-coated copper foil, aluminum foil or carbon-coated aluminum foil.

[0056] The sodium metal negative electrode is a metal sodium foil, and the thickness thereof is 35-1000 μm, preferably 300-800 μm, and more preferably 600-800 μm.

[0057] The present invention does not specifically limit the material of the non-sodium metal negative electrode, and can be used for the negative electrode of a sodium ion battery, such as carbon-based materials, alloy materials, transition metal compounds and organic compounds, such as graphite, graphene, hard carbon, soft carbon, sodium alloy materials (sodium indium alloy, sodium silicon alloy, sodium tin alloy, sodium lead alloy, sodium phosphorus alloy, sodium arsenic alloy, sodium antimony alloy, sodium bismuth alloy), titanium-based materials, disodium terephthalate, etc.

[0058] In one embodiment of the present invention, the sodium ion battery comprises a positive electrode, an electrolyte, a separator and a sodium metal negative electrode, wherein the electrolyte is one of the electrolytes for sodium ion batteries described in the first aspect, and the assembled sodium ion battery is a sodium ion half-cell. The material of the positive electrode of the sodium ion half-cell is a carbon-coated aluminum foil, a sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NFM), sodium ferromanganate, sodium nickel ferromanganate, sodium vanadium phosphate, sodium ferric pyrophosphate, sodium vanadium fluorophosphate or sodium ferric fluorophosphate.

[0059] In the sodium ion half-cell, the ratio of the mass of the electrolyte to the capacity of the battery is 1-10 g / Ah, preferably 2-6 g / Ah, and more preferably 2-4 g / Ah.

[0060] The operating temperature of the sodium ion half-cell is -30°C to 70°C, preferably -25°C to 65°C, and more preferably -20°C to 60°C.

[0061] When the positive electrode material is carbon-coated aluminum foil, the operating cutoff voltage of the sodium ion half-cell is 1.0V.

[0062] When the positive electrode material is carbon-coated aluminum foil, the deposition-stripping coulombic effect of the sodium ion half-cell is greater than 80%, preferably greater than 90%, and more preferably greater than 99.5%.

[0063] In one embodiment of the present invention, the sodium ion battery comprises a positive electrode, an electrolyte, a separator and a negative electrode current collector, the electrolyte is one of the electrolytes for sodium ion batteries described in the first aspect, and the assembled sodium ion battery is a negative electrode-free sodium ion battery. The negative electrode-free sodium ion battery in the present invention comprises a positive electrode, an electrolyte, a separator and a negative electrode current collector. During the first charging process, a sodium metal layer is deposited on the negative electrode current collector to form a sodium metal negative electrode.

[0064] In the negative electrode-free sodium ion battery, the present invention does not specifically limit the positive electrode, and any positive electrode material that can be used for a sodium ion battery can be used. For example, one of an oxide-type positive electrode material, a polyanion-type positive electrode material, a Prussian blue positive electrode material, a Prussian white positive electrode material, and an organic positive electrode material, preferably one of a metal oxide-type positive electrode material and a phosphate-based polyanion-type positive electrode material, specifically a sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NFM), sodium iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium iron pyrophosphate, sodium vanadium fluorophosphate or sodium iron fluorophosphate, preferably a sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2, NFM) or sodium vanadium phosphate.

[0065] In the negative electrode-free sodium ion battery, for button cells, the amount of the electrolyte is 10-100 μL, preferably 10-80 μL, and more preferably 30-50 μL. For soft-pack batteries, the ratio of the mass of the electrolyte to the capacity of the battery is 1-10 g / Ah, preferably 2-8 g / Ah, and more preferably 2-4 g / Ah.

[0066] In the negative electrode-free sodium ion battery, the single-surface area ratio of the negative electrode current collector to the positive electrode is (1.0-2.0):1, preferably (1.0-1.5):1, and more preferably (1.1-1.2):1.

[0067] The operating temperature of the negative electrode-free sodium ion battery is -30°C to 70°C, preferably -25°C to 65°C, and more preferably -20°C to 60°C.

[0068] When the positive electrode material is layered oxide NFM, the operating voltage of the negative electrode-free sodium ion battery is above 3.2V, preferably above 3.5V, more preferably above 3.8V, such as 4V.

[0069] When the positive electrode material is a layered oxide NFM, the capacity retention rate of the negative electrode-free sodium ion battery is 65% or more, preferably 75% or more, and more preferably 80% or more.

[0070] When the positive electrode material is layered oxide NFM, at -20 to 60°C, the mass specific capacity of the negative electrode-free sodium ion battery is 40-180 mAh / g, preferably 50-160 mAh / g, and more preferably 90-160 mAh / g.

[0071] In another embodiment of the present invention, the sodium ion battery comprises a positive electrode, an electrolyte, a separator and a non-sodium metal negative electrode, the electrolyte is one of the electrolytes for sodium ion batteries described in the first aspect, and the assembled sodium ion battery is a non-sodium metal negative electrode sodium ion battery.

[0072] In the sodium ion battery with a non-sodium metal negative electrode, the present invention does not specifically limit the positive electrode thereof, and any positive electrode material that can be used for a sodium ion battery can be used. For example, one of an oxide-type positive electrode material, a polyanion-type positive electrode material, a Prussian blue positive electrode material, a Prussian white positive electrode material, and an organic positive electrode material, preferably one of a metal oxide-type positive electrode material and a phosphate-based polyanion-type positive electrode material, specifically, a sodium ion layered oxide (NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NFM), sodium iron manganate, sodium nickel iron manganate, sodium vanadium phosphate, sodium iron pyrophosphate, sodium vanadium fluorophosphate or sodium iron fluorophosphate, preferably a sodium ion layered oxide (NaNi1 / 3 Fe 1 / 3 Mn 1 / 3 O2, NFM) or sodium vanadium phosphate.

[0073] In the sodium ion battery with non-sodium metal negative electrode, for button batteries, the amount of the electrolyte is 10-100 μL, preferably 10-80 μL, and more preferably 30-50 μL. For soft-pack batteries, the ratio of the mass of the electrolyte to the capacity of the battery is 1-10 g / Ah, preferably 2-8 g / Ah, and more preferably 2-4 g / Ah.

[0074] In the non-sodium metal negative electrode sodium ion battery, the single-surface area ratio of the non-sodium metal negative electrode to the positive electrode is (1.0-2.0):1, preferably (1.0-1.5):1, and more preferably (1.1-1.2):1.

[0075] The operating temperature of the non-sodium metal negative electrode sodium ion battery is -30°C to 70°C, preferably -25°C to 65°C, and more preferably -20°C to 60°C.

[0076] The operating voltage of the non-sodium metal negative electrode sodium ion battery is above 3.0V, preferably above 3.3V, and more preferably above 3.6V.

[0077] The fourth aspect of the present invention also provides a method for preparing the sodium ion battery, which is carried out under a protective atmosphere, such as an atmosphere deoxygenated and dehydrated, preferably an atmosphere with water and oxygen contents less than 0.1 ppm, such as an argon atmosphere.

[0078] The interior of the sodium-ion half-cell is assembled in the order of positive electrode, separator, sodium metal negative electrode or negative electrode current collector, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the sodium metal negative electrode.

[0079] The interior of the negative electrode-free sodium-ion battery is assembled in the order of positive electrode, separator, and negative electrode current collector, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the negative electrode current collector.

[0080] The non-sodium metal negative electrode sodium ion battery is assembled in the order of positive electrode, separator, and non-sodium metal negative electrode, and electrolyte is dripped between the positive electrode and the separator, and between the separator and the non-sodium metal negative electrode.

[0081] The manufacturing methods of the positive electrode sheet, the separator, the sodium metal negative electrode, the negative electrode current collector and the non-sodium metal negative electrode in the present invention can be carried out according to the general methods in the art.

[0082] Example

[0083] The following specifically discloses the embodiments of the sodium ion battery electrolyte and the sodium ion battery of the present application. The embodiments and the accompanying drawings are only exemplary and do not constitute any limitation to the protection scope of the present invention.

[0084] Example 1

[0085] Prepare electrolyte in a glove box with argon atmosphere, add 1g molecular sieve (4A molecular sieve, commercially available, many manufacturers) to 5mL diethylene glycol dibutyl ether, let stand for 24h, filter out the molecular sieve, and obtain dehydrated diethylene glycol dibutyl ether. Add sodium tetrafluoroborate to the dehydrated diethylene glycol dibutyl ether, add sodium hexafluorophosphate to dissolve it after it is fully dissolved, so that the concentration of sodium hexafluorophosphate is 1.2mol / L and the concentration of sodium tetrafluoroborate is 0.6mmol / L, then add an appropriate amount of metallic sodium to soak for secondary dehydration, take the supernatant, and obtain electrolyte 1#.

[0086] Example 2-3

[0087] Electrolyte 2# and electrolyte 3# were prepared according to the method of Example 1, with the only difference being that the concentrations of sodium hexafluorophosphate were 1.0 mol / L and 0.8 mol / L respectively, and the concentration of sodium tetrafluoroborate was 0.6 mmol / L.

[0088] Embodiment 4-7

[0089] Electrolytes 4#-7# were prepared according to the method of Example 1, except that: electrolytes 4#-7# were prepared using a mixed solvent of diethylene glycol dibutyl ether and ethylene glycol dibutyl ether as solvents. In electrolytes 4#-7#, the concentrations of sodium hexafluorophosphate were 1.0 mol / L, 1.0 mol / L, 0.8 mol / L, and 0.5 mol / L, respectively, the concentration of sodium tetrafluoroborate was 0.6 mmol / L, and the volume ratios of diethylene glycol dibutyl ether and ethylene glycol dibutyl ether were 80:20, 60:40, 50:50, and 40:60, respectively.

[0090] Examples 8-10

[0091] Electrolytes 8#-10# were prepared according to the method of Example 1, except that diethylene glycol dibutyl ether was used as solvent and sodium hexafluorophosphate was used as solute, and the concentrations of sodium hexafluorophosphate were 1.2 mol / L, 1.0 mol / L, and 0.8 mol / L, respectively.

[0092] Comparative Example

[0093] Comparative Example 1

[0094] Electrolyte 11# was prepared according to the method of Example 1, except that: electrolyte 11# was prepared using diethylene glycol dibutyl ether as solvent and sodium bis(fluoromethanesulfonyl)imide as solute, wherein the concentration of sodium bis(fluoromethanesulfonyl)imide was 1 mol / L.

[0095] Comparative Example 2

[0096] Electrolyte 12# was prepared according to the method of Example 1, except that: electrolyte 12# was prepared using diethylene glycol dibutyl ether as solvent and sodium bis(trifluoromethylsulfonyl)imide as solute, wherein the concentration of sodium bis(trifluoromethylsulfonyl)imide was 1 mol / L.

[0097] Comparative Example 3

[0098] Electrolyte 13# was prepared according to the method of preparing electrolyte 9# in Example 9, except that an equal volume of ethylene glycol dibutyl ether was used instead of diethylene glycol dibutyl ether. The concentration of sodium hexafluorophosphate was 1.0 mol / L.

[0099] Comparative Example 4

[0100] Electrolyte 14# was prepared according to the method for preparing electrolyte 9# in Example 9, except that an equal volume of dibutyl ether was used instead of diethylene glycol dibutyl ether, and the concentration of sodium hexafluorophosphate was 0.5 mol / s.

[0101] Table 1 Solvents and solutes of electrolyte 1# to electrolyte 14#

[0102]

[0103] Experimental example

[0104] Experimental Example 1

[0105] CR2032 button cells were assembled in an argon-filled glove box, with metal sodium foil (Aladdin sodium ingot, 600 μm sodium foil obtained by roller pressing) as the negative electrode, carbon-coated aluminum foil (manufacturer Kelude, carbon layer double-sided coating, carbon coating layer thickness 1 μm + aluminum foil thickness 18 μm + carbon coating layer thickness 1 μm) as the positive electrode current collector, Al2O3@Celgard (manufacturer Kelude, Al2O3 layer 9 μm + Celgard layer 3 μm) as the separator, and carbon-coated aluminum foil||Na half-cells were assembled with electrolyte 1# to electrolyte 14#, wherein the amount of electrolyte used was 40 μL, to obtain sodium metal half-cells 1# to 14#.

[0106] Experimental Example 2

[0107] The layered oxide positive electrode material (NFM) (manufacturer Shenzhen Kejing, model XN25S), conductive agent carbon black (SuperP) (manufacturer Shenzhen Kejing, model Super Li) and binder (polyvinylidene fluoride PVDF, (manufacturer Shenzhen Kejing, HSV900)) were mixed and ground, the mass ratio of NFM, Super P and PVDF was (95.5%: 2.5%: 2%), N-methyl-2-pyrrolidone (NMP) was added to the above mixture as a solvent, the mass volume ratio of the mixture of NFM, Super P and PVDF to NMP was 2.5g solid mixture: 1mL NMP, and the mixture was stirred until there was no particle feeling to obtain a mixed slurry, and the mixed slurry was coated on an aluminum foil (manufacturer Saibo, mass purity 99.99%), and the NFM positive electrode sheet was obtained after drying and rolling. The mass loading of the mixture of NFM, Super P and PVDF on the aluminum foil was 430g / cm 2 .

[0108] Carbon-coated aluminum foil (manufacturer Cyber, double-sided coating) was used as the negative electrode current collector, the above-mentioned NFM positive electrode sheet was used as the positive electrode, Al2O3@Celgard was used as the separator (manufacturer Cyber, Al2O3 layer 9μm + Celgard layer 3μm), electrolyte 1# to electrolyte 14# were used as electrolytes, and the amount of electrolyte was 40μL, respectively, to assemble CR2032 button-type carbon-coated aluminum foil || NFM full batteries, and obtain button-type negative electrode-free sodium ion batteries 1# to 14#.

[0109] Experimental Example 3

[0110] A carbon-coated aluminum foil (manufacturer Cyber, double-sided coating: 1+18+1, i.e., carbon coating layer thickness 1 μm + aluminum foil thickness 18 μm + carbon coating layer thickness 1 μm) was used as the negative electrode current collector, the NFM positive electrode sheet prepared in Experimental Example 2 was used as the positive electrode, Al2O3@ / Celgard was used as the separator, and electrolyte 1# to electrolyte 14# were used as electrolytes, respectively, with an electrolyte dosage of 4 g / Ah, to assemble carbon-coated aluminum foil||NFM soft-pack full cells to obtain soft-pack negative electrode-free sodium ion batteries 1# to 14#.

[0111] Experimental Example 4

[0112] A hard carbon negative electrode (the hard carbon negative electrode is prepared according to the battery negative electrode sheet preparation method in Example 9 in Chinese patent CN116924389A) is used as the non-sodium metal negative electrode, the NFM positive electrode sheet prepared in Experimental Example 2 is used as the positive electrode, Al2O3@Celgard is used as the separator, and electrolyte 1# to electrolyte 14# are used as electrolytes, respectively, with an electrolyte dosage of 40 μL, to assemble button-type non-sodium metal negative electrode sodium ion batteries 1# to 14#.

[0113] Experimental Example 5

[0114] The coulombic efficiency (sodium deposition / stripping efficiency) of sodium metal half-cells 1# to 14# was tested respectively. The test method is as follows. The test results are shown in Table 2.

[0115] Sodium metal half-cells 1# to 14# were placed in thermostats at -20°C, 25°C, and 60°C for 2 h, respectively, at 0.2 mA / cm 2 (-20℃) and 1mA / cm 2 (25℃ and 60℃) discharge deposition with current density 1mAh / cm 2 The specific area capacity is then measured at 1 mA / cm 2 Charge at a current density of 1.0V and record the charge capacity at this time;

[0116] Coulomb efficiency (sodium deposition / stripping efficiency) = discharge capacity / charge capacity × 100%

[0117] From the data in Table 2, it can be seen that compared with the sodium metal half-cells using electrolytes 1#-10#, the coulombic efficiency of the sodium ion half-cells 11#-12# using electrolytes 11# and 12# is greatly reduced, indicating that the use of a solvent containing diethylene glycol dibutyl ether to obtain an electrolyte is beneficial to improving the coulombic efficiency of the battery.

[0118] By comparing the data of sodium metal half-cells 1#~2# and sodium ion half-cells 8#~9#, it can be seen that when the concentration of sodium hexafluorophosphate is not less than 1.0 mol / L, adding sodium tetrafluoroborate electrolyte is beneficial to improving the coulombic efficiency; when the concentration of sodium hexafluorophosphate is not less than 1.0 mol / L, the increase in its concentration is beneficial to the improvement of the coulombic efficiency, and when its concentration is reduced to no more than 0.8 mol / L, the coulombic efficiency decreases.

[0119] Comparing the data of sodium metal half-cell 2# and sodium metal half-cell 4#~5#, it can be seen that when ethylene glycol dibutyl ether is added to the electrolyte, the coulombic efficiency is reduced to a certain extent. The higher the proportion of ethylene glycol dibutyl ether added, the more the coulombic efficiency is reduced. It shows that using diethylene glycol dibutyl ether as the electrolyte solvent is more conducive to improving the performance of sodium ion batteries. Comparing sodium metal half-cell 9# and sodium ion half-cells 13# and 14#, it can be seen that due to the poor oxidation stability of ethylene glycol dibutyl ether and dibutyl ether, and the low solubility in sodium hexafluorophosphate, the coulombic efficiency of the deposition / stripping of the sodium metal negative electrode of the electrolyte with single solvent ethylene glycol dibutyl ether and dibutyl ether as solvent is low, and due to the oxidative decomposition of the electrolyte, the sodium ion full battery without the negative electrode cannot be charged and discharged normally due to the oxidative decomposition of the electrolyte.

[0120] According to the above method, the coulombic efficiency statistics of sodium metal half-cell 1# obtained by deposition / stripping tests at -20℃, 25℃ and 60℃ are shown in the figure below: Figure 1 As shown, from Figure 1 It can be seen that the coulombic efficiency of sodium metal half-cell 1# can reach 99.8% after 100 cycles at a temperature of -20℃ to 60℃.

[0121] Experimental Example 6

[0122] After 10 cycles of charge and discharge at -20°C, 25°C, and 60°C, the sodium metal half-cell 1# deposited 2 mAh cm -2 After the area specific capacity was measured, the SEM images of the Na metal negative electrode of the sodium metal half-cell 1# were tested. Figure 2 As shown. Under various temperature conditions, the sodium metal negative electrode presents a uniform and dense deposition morphology.

[0123] Experimental Example 7

[0124] The button-type negative electrode-free sodium ion batteries 1#~14# were first placed in a constant temperature box at 25°C for 24 hours, then placed in a constant temperature box at -20°C for 2 hours, charged to 4.1V at a current density of 7.5mA / g, and then discharged to 2.0V at a current density of 7.5mA / g. The discharge capacity at this time was recorded and the mass specific capacity was calculated.

[0125] The button-type negative electrode-free sodium ion batteries 1# to 14# were placed in a constant temperature box at 25°C, left to stand for 24 hours, charged to 4.0V at a current density of 30mA / g, and then discharged to 2.0V at a current density of 30mA / g. The discharge capacity at this time was recorded and the mass specific capacity was calculated.

[0126] The button-type negative electrode-free sodium ion batteries 1# to 14# were placed in a constant temperature box at 60°C, left to stand for 24 hours, charged to 4.0V at a current density of 30mA / g, and then discharged to 2.0V at a current density of 30mA / g. The discharge capacity at this time was recorded and the mass specific capacity was calculated.

[0127] The charge and discharge curves of button-type negative electrode-free sodium ion battery 1# under the above test conditions are as follows: Figure 3 shown.

[0128] The test results of button-type negative electrode-free sodium ion batteries 1# to 14# are shown in Table 2.

[0129] From the data in Table 2, it can be seen that compared with the button-type negative electrode-free sodium ion batteries using electrolytes 1#-10#, the mass specific capacity of button-type negative electrode-free sodium ion batteries 11#-12# using electrolytes 11# and 12# is greatly reduced. This shows that the use of a solvent containing diethylene glycol dibutyl ether to obtain an electrolyte is beneficial to improving the discharge specific capacity of the battery.

[0130] Comparing the data of button-type sodium ion battery 2# without negative electrode and button-type sodium ion battery 4#~5# without negative electrode, it can be seen that when ethylene glycol dibutyl ether is added to the electrolyte, the mass specific capacity is reduced to a certain extent. The higher the proportion of ethylene glycol dibutyl ether added, the more the mass specific capacity is reduced. This shows that using diethylene glycol dibutyl ether as the electrolyte solvent is more conducive to improving the performance of sodium ion batteries. Comparing button-type sodium ion batteries 13# and 14# without negative electrode, it can be seen that due to the poor oxidation stability of ethylene glycol dibutyl ether and dibutyl ether, and the low solubility in sodium hexafluorophosphate, the coulomb efficiency of the deposition / stripping of the sodium ion negative electrode of the electrolyte with single solvent ethylene glycol dibutyl ether and dibutyl ether as solvent is low, and the sodium ion full battery without negative electrode cannot be charged and discharged normally due to the oxidation decomposition of the electrolyte.

[0131] From the data in Table 2, it can be seen that the specific capacity of button-type negative electrode-free sodium ion batteries 1#~2# is higher than that of other button-type negative electrode-free sodium ion batteries. By comparing button-type negative electrode-free sodium ion batteries 1# and 2#, it can be seen that appropriately reducing the concentration of sodium hexafluorophosphate can improve the low temperature (-20°C) performance of the battery, but the performance at 25-60°C is slightly reduced. By comparing button-type negative electrode-free sodium ion batteries 1#~2# and button-type negative electrode-free sodium ion batteries 8#~9#, it can be seen that adding sodium tetrafluoroborate to the electrolyte can improve the mass specific capacity of the battery to a certain extent.

[0132] Experimental Example 8

[0133] The button-type negative electrode-free sodium ion batteries 1# to 14# were placed in a constant temperature box at 25°C for 2 hours, charged to 4.0V at a current density of 30mA / g, and then discharged to 2.0V at a current density of 30mA / g, and the charge and discharge capacities at this time were recorded;

[0134] 100-cycle capacity retention rate = discharge capacity of the 100th charge-discharge cycle at 25° C. / discharge capacity of the first charge-discharge cycle at 25° C.×100%.

[0135] The test results are shown in Table 2.

[0136] From the data in Table 2, it can be seen that compared with the button-type negative electrode-free sodium ion batteries using electrolytes 1#-10#, the capacity retention rate of button-type negative electrode-free sodium ion batteries 11#-12# using electrolytes 11# and 12# is greatly reduced. This shows that the use of a solvent containing diethylene glycol dibutyl ether to obtain an electrolyte is beneficial to improving the capacity retention rate of the battery.

[0137] Comparing the data of button-type sodium-ion battery 2# without negative electrode and button-type sodium-ion battery 4#~5# without negative electrode, it can be seen that when ethylene glycol dibutyl ether is added to the electrolyte, the capacity retention rate is reduced to a certain extent. The higher the proportion of ethylene glycol dibutyl ether added, the more the mass specific capacity is reduced. This shows that using diethylene glycol dibutyl ether as the electrolyte solvent is more conducive to improving the performance of sodium-ion batteries.

[0138] By comparing button-type negative electrode-free sodium-ion batteries 13# and 14#, it can be seen that due to the poor oxidation stability of ethylene glycol dibutyl ether and dibutyl ether and the low solubility in sodium hexafluorophosphate, the coulombic efficiency of the sodium-ion half-cell with single-solvent ethylene glycol dibutyl ether and dibutyl ether as the electrolyte is low, and the negative electrode-free sodium-ion full battery cannot be charged and discharged normally due to the oxidative decomposition of the electrolyte.

[0139] From the data in Table 2, it can be seen that the capacity retention rate of button-type negative electrode-free sodium ion batteries 1#, 2#, and 8# is higher than that of other button-type negative electrode-free sodium ion batteries. By comparing button-type negative electrode-free sodium ion batteries 1#~2# and button-type negative electrode-free sodium ion batteries 8#~9#, it can be seen that adding sodium tetrafluoroborate to the electrolyte can improve the mass specific capacity of the battery to a certain extent.

[0140] Table 2 Battery performance test results

[0141]

[0142]

[0143] Experimental Example 9

[0144] The soft-pack negative electrode-free sodium ion battery 1# was placed in a constant temperature box at 25°C for 24 hours, charged to 4.0V at a current density of 100mA, and then discharged to 2.0V at a current density of 100mA to test its cycle stability, and the charge and discharge curves of the 1st and 100th cycles were recorded. Figure 4 The initial discharge capacity of the soft pack battery in the first cycle can reach 1.43Ah. After 100 stable cycles, its capacity can reach 1.18Ah, and the capacity retention rate is as high as 83%.

[0145] The embodiments of the present invention have been described above, but these are only typical examples, so the present invention is not limited thereto, and it is easy for a person skilled in the art to understand that various modes can be considered without changing the spirit of the present invention.

Claims

1. An electrolyte for a sodium ion battery, prepared from a raw material comprising an ether solvent and a sodium salt, The ether solvent includes one or more of the ether compounds represented by the general formula (1), in, R1 and R2 are each independently selected from an alkyl group having a carbon number greater than 1, and n is an integer of 1-10, Optionally, the ether solvent further comprises one or more of the ether compounds represented by the general formula (2), Wherein, R3 and R4 are each independently selected from an alkyl group having a carbon number greater than 1, and m is an integer of 1-10. The sodium salt is selected from one or more of sodium fluoride.

2. The electrolyte according to claim 1, characterized in that R1 and R2 are each independently selected from an alkyl group having 4 to 6 carbon atoms, preferably a butyl group or a pentyl group, and n is an integer of 1 to 5, preferably 1, 2 or 3. R3 and R4 are each independently selected from an alkyl group having a carbon number of 2-7, preferably propyl, butyl, pentyl or hexyl, and m is an integer of 1-5, preferably 1, 2 or 3.

3. The electrolyte according to claim 1, characterized in that The ether solvent is selected from one or more ether compounds represented by general formula (1), Among them, R1 and R2 are each independently selected from an alkyl group containing a carbon number greater than 1, preferably an alkyl group containing a carbon number of 2-6, more preferably propyl, butyl, pentyl or hexyl, and more preferably, R1 and R2 are both n-butyl; n is an integer of 1-10, preferably an integer of 1-5, and more preferably 1, 2 or 3.

4. The electrolyte according to claim 1, characterized in that The sodium salt is selected from one or more inorganic sodium fluoride salts, preferably one or more of sodium hexafluoroarsenate, sodium hexafluorophosphate and sodium tetrafluoroborate, more preferably sodium hexafluorophosphate and / or sodium tetrafluoroborate.

5. A method for preparing an electrolyte for a sodium ion battery according to claim 1, characterized in that: In the method, the raw materials include the ether solvent and the sodium salt, Under a protective atmosphere, the sodium salt is added to the ether solvent after the first dehydration to dissolve and obtain solution I. Preferably, the solution is dehydrated for a second time to obtain an electrolyte.

6. A sodium ion battery, characterized in that: The invention comprises a positive electrode, an electrolyte and a diaphragm, wherein the electrolyte is one of the electrolytes for sodium ion batteries according to any one of claims 1 to 4.

7. The sodium ion battery according to claim 6, characterized in that: The sodium ion battery further includes a negative electrode current collector, a sodium metal negative electrode or a non-sodium metal negative electrode.

8. The sodium ion battery according to claim 6, characterized in that: In the sodium ion battery, the ratio of the mass of the electrolyte to the capacity of the sodium ion battery is 1-10 g / Ah, preferably 2-8 g / Ah, and more preferably 2-4 g / Ah. The operating temperature of the sodium ion battery is -30°C to 70°C, preferably -25°C to 65°C, and more preferably -20°C to 60°C.

9. The sodium ion battery according to claim 6, characterized in that: The sodium ion battery comprises a positive electrode, an electrolyte, a separator and a sodium metal negative electrode, and the assembled sodium ion battery is a sodium ion half-cell, or The sodium ion battery comprises a positive electrode, an electrolyte, a separator and a negative electrode current collector, and the assembled sodium ion battery is a negative electrode-free sodium ion battery, or The sodium ion battery comprises a positive electrode, an electrolyte, a separator and a non-sodium metal negative electrode, and the assembled sodium ion battery is a non-sodium metal negative electrode sodium ion battery.

10. A method for preparing a sodium ion battery according to any one of claims 6 to 9, characterized in that: The method is carried out under a protective atmosphere. The battery is assembled in the order of a positive electrode, a separator, and a sodium metal negative electrode, and the electrolyte for a sodium ion battery according to any one of claims 1 to 4 is dripped between the positive electrode and the separator, and between the separator and the sodium metal negative electrode; The battery is assembled in the order of positive electrode, separator, and negative electrode current collector, and the electrolyte according to any one of claims 1 to 4 is dripped between the positive electrode and the separator, and between the separator and the negative electrode current collector. The battery is assembled in the order of a positive electrode, a separator, and a non-sodium metal negative electrode, and the electrolyte according to any one of claims 1 to 4 is dripped between the positive electrode and the separator, and between the separator and the non-sodium metal negative electrode.

Citation Information

Patent Citations

  • Hard carbon, preparation method thereof and sodium ion battery prepared from hard carbon

    CN116924389A